Rule violations by SMEs: The influence of conduct within the industry, company culture and personal motives - Peeters, Marlijn (European journal of criminology, 2020)
The literature suggests many different variables that may explain rule violations by companies. These can be categorized into variables at the industry level, such as the degree of rule violations, at the company level, such as the organizational culture, and at the individual level, such as personal or social norms. From the Dutch Tax Administration's (2009) registration data, industries were selected with relatively low and relatively high tax correction rates. Within these industries, small and medium-sized enterprises (SMEs) with 20-150 employees were selected that either had received no (or negative) corrections or had received large positive corrections, resulting in a population of 1558 companies. In 194 of these SMEs, both the director and an employee were interviewed about violations of administrative, environmental and tax obligations, about their personal motives and about the ethical organizational culture. The results of the study show that all three levels of variables explain intentions to comply or to violate the rules. Ethical culture contributes to explaining the compliance intentions of both directors and employees. However, in contrast to previous research, about half of the SMEs cannot be characterized by a coherent ethical culture.